2018
DOI: 10.1007/s12029-018-0156-6
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Cancer Stem Cell Markers (Notch1, ALDH1, and CD44) in Primary Colorectal Carcinoma

Abstract: Expression of stem cell markers ALDH1, Notch1, and CD44 correlates with poor prognosis in a CRC and represents an independent prognostic factor. They are associated with a feature of epithelial-mesenchymal transition evidenced by their association with high tumor burden.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 34 publications
8
28
0
Order By: Relevance
“…High ALDH activity has been shown to support clonogenic property in CRC cells and generate cells with enhanced stem cell properties [36]. In addition, elevated ALDH levels in CRC patients has a strong association with inferior prognosis [37]. In our study, knockdown of OPN restricted the ALDH1 high CSCs ratio, which suggests that OPN is implicated in the “stemness” of CRC cells.…”
Section: Discussionsupporting
confidence: 53%
“…High ALDH activity has been shown to support clonogenic property in CRC cells and generate cells with enhanced stem cell properties [36]. In addition, elevated ALDH levels in CRC patients has a strong association with inferior prognosis [37]. In our study, knockdown of OPN restricted the ALDH1 high CSCs ratio, which suggests that OPN is implicated in the “stemness” of CRC cells.…”
Section: Discussionsupporting
confidence: 53%
“…Of these studies, 30 studies that evaluated the prognostic role of CD44 in CRC patients were in accordance with the inclusion criteria (2428, 34–57, 66). Thirty four studies reported the association of CD44 expression with clinicopathological features (24, 26, 27, 35, 3942, 44, 46, 47, 49, 52, 54, 57, 6784).…”
Section: Resultsmentioning
confidence: 99%
“…ALDH1 expression is associated with colon cancer location [73], with advanced stages of the disease [75], with number of lymph nodes involved (N) [73,75,76], and with perivenous invasion (V) [73] but also with local tumor recurrence [75]. The association between ALDH1 expression and lymph node involvement was not seen by Zhou et al [74].…”
Section: Author Detailsmentioning
confidence: 99%
“…Recently, ALDH1 expression was found to be involved in epithelial-mesenchymal transition (EMT) and could play, thus, a role in cancer progression and distant metastases formation [75][76][77].…”
Section: Author Detailsmentioning
confidence: 99%
See 1 more Smart Citation